Nilai-Nilai Religiusitas Web Series Between Two Sides (BTS) pada Channel Youtube Hijab Alila - Gina Hafiza; Irfan Safrudin; Hendi Suhendi (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. This research discusses the religiosity values ​​of the web series "Between Two Sides (BTS)" on the Hijab Alila YouTube channel, which aims to determine the values ​​of aqidah, moral values ​​and sharia values ​​contained in the web series "Between Two Sides (BTS)". Meanwhile, the benefits are expected to increase scientific insight for research development at the Faculty of Da'wah. This research uses Roland Barthes' semiotic analysis theory which aims to reveal the meaning of denotation, connotation and myth contained in the web series. The method used is a qualitative method with a descriptive approach. Data collection techniques were obtained from content analysis methods and literature studies. The findings from this research are that the web series "Between Two Sides (BTS)" contains the values ​​of religiosity, aqidah, morals and sharia. Aqidah values ​​discuss faith and belief, maintaining relationships with non-muhrim and the importance of maintaining faith. Moral values ​​include balance in life, selectiveness in choosing friends, open attitude, self-control and so on. On sharia values ​​regarding the use of the hijab for Muslim women and the command not to delay prayer. Abstrak. Penelitian ini membahas tentang nilai-nilai religiusitas web series “Between Two Sides (BTS)” pada channel youtube Hijab Alila, yang bertujuan untuk mengetahui nilai aqidah, nilai akhlak dan nilai syariah yang terdapat pada web series “Between Two Sides (BTS)”. Sedangkan manfaatnya diharapkan dapat menambah wawasan keilmuan bagi pengembangan penelitian di Fakultas Dakwah. Penelitian ini menggunakan teori analisis semiotika Roland Barthes yang bertujuan mengungkap makna denotasi, konotasi dan mitos yang terdapat pada web series tersebut. Metode yang digunakan adalah metode kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data diperoleh dari metode analisis isi dan studi literatur. Temuan dari penelitian ini bahwa web series “Between Two Sides (BTS)” ini mengandung nilai religiusitas aqidah, akhlak dan syariah. Nilai aqidah membahas tentang keimanan dan keyakinan, menjaga hubungan dengan non muhrim dan pentingnya menjaga iman. Nilai akhlak mencakup keseimbangan dalam hidup, selektif dalam memilih teman, sikap terbuka, pengendalian diri dan lain sebagainya. Pada nilai syariah mengenai penggunaan hijab pada muslimah dan perintah tidak menunda shalat.